Response of several levels of water and organic fertilizer application to the growth of Chili (Capsicum annum L.) Aka variety in the vegetative phase - Rahman, Doni; R, Renfiyeni; Ilham, Dewi Jayagma; Budiyanti, Tri (Jurnal Sains Agro, 2024)
ABSTRACTWater stress disrupts plant growth, especially chili plants, which results in decreased yields, crop failure or plant death. One strategy to increase chili plant tolerance can be done through fertilization, organic fertilizer, mycorrhiza and other microorganisms. The study aims to determine the effect of several levels of water supply and organic fertilizer on the growth of curly chili varieties AKA in the early vegetative and generative phases. The study used a complete randomized block design with 12 treatments with 3 replications. The treatments are: P0. Field capacity water supply, P1. Field capacity water irrigation (FC) + 60ml cow urine, P2. Water irrigation FC + 10ml/L amiboost, P3. FC water irrigation + 15g mycorrhiza, P4. 50% FC water irrigation, P5. 50% field capacity water irrigation + 60ml cow urine, P6. 50% FC + amiboost 10ml/L, P7. 50% FC water irrigation + mycorrhiza 15g, P8. 25% FC water irrigation, P9. 25% FC water irrigation + cow urine 60ml, P10. 25% FC water irrigation + amiboost 10ml/L, P11.  25% FC water irrigation + mycorrhiza 15g. The results showed that watering with water below 50% FC reduced plant growth in the early vegetative and generative phases. This can be seen in all observed variables, decreasing significantly. The growth of plants given 100% FC water was very good, especially in the treatment of adding amiboost and cow urine. The addition of liquid organic fertilizer and mycorrhiza to plants given water below 50% KL has not been able to increase the growth of chili plants at the age of 2 months after planting.